Factors Related to Defaulters and Treatment Failure of tuberculosis Patients in the DOTS Program in the Sunsari District of Eastern Nepal - Lamsal, DK; Lewis, OD; Smith, S; Jha, N (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Objectives : The aim of this study was to investigate reasons underlying failure to complete DOTS treatment in TB patients in Dharan and the Sunsari district of eastern Nepal. Methods : A descriptive, qualitative study using semi structured questionnaires after identifying cases from register data. Results were then compared with the results of informal recorded discussions, direct observation, and focus group discussions. All defaulter and treatment failure TB patients in the DOTS program in Sunsari district from July 2002 to July 2003 were included in the study. Results : All of the defaulter patients in this study were struggling financially, and said that they had trouble leaving work to go to the DOTS centre, as well as difficulty with distance and transport. Other issues such as alcohol, stigma, poverty, inadequate education and the use of private clinics and traditional healers were discussed. Conclusion : Almost half the Nepalese population is infected with TB. Despite meeting the WHO goals for default and treatment failure it is important to aggressively address those aspects that can be changed so the country can continue to reduce the burden of TB on its community. Recommendations are made from the results of this study that may help improve adherence to DOTS programmes. Keywords : tuberculosis; Nepal; DOTS; defaulter; compliance DOI: 10.3126/saarctb.v6i1.3061 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (1) 25-30